Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T17:23:10+01:00
A)
2x= 1 - 3y
0,5x= 2 - y /*2

2x=1-3y
x=4-2y

2(4-2y)=1-3y
x=4-2y

8-4y=1-3y
x=4-2y

-y=-7
x=4-2*7

y=7
x=-10

b)
x- y - 3=0 /*3
2x+3y-11=0

3x-3y-9=0
2x+3y-11=0
--------------+

2x-20=0
2x=20
x=10

x- y - 3=0
x=10

10-3=y
x=10

y=7
x=10

c)
-3(x+2) + 2(x+y) = 2
2(y+2) + 3(x-y) = 2x-1

-3x-6+2x+2y=2
2y+4+3x-3y=2x-1

-x+2y=2+6
x-y=-5
------------+
y=3
x=-5+y

y=3
x=-2


2010-03-04T17:31:48+01:00
A) 2x = 1-3y
0.5x = 2-y /razy 2

2x = 1- 3y
x = 4 - 2y

2 (4-2y)= 1- 3y
8-4y = 1- 3y
8 - 1 = 3y + 4y
7 = 7y / dzielimy przez 7

y= 1
x = 2

b) x-y - 3 = 0
2x +3y -11 = 0

x= y+3
2 (3+y) +3y - 11=0

x= y+3
6 +2y +3y-11=0

5y -5=0 / +5
5y = 5

y = 1
x= 4

c) -3(x+2) + 2(x+y) = 2
2(y+2) + 3(x-y) = 2x-1

- 3x - 6+2x+2y=2
2y+4+3x-3y =2x-1

-x -6+2y=2
-y +4 +3 =2x-1

-6 +2y-2=x
y =4+3-2x+1

y = 2(-6 +2y-2) +3+4+1
y= -12 +4y-4+8
8= 3y

y = 2 i 2/3
x= -3 i 1/3